Informal trading in South Africa: the experiences of African informal migrant traders operating in Pretoria central - Muchuweni-Chiumira, Mufaro (My University, 2019)
Globally, migrants from low-income countries tend to seek opportunities from developed countries. In Southern Africa, where poverty and unemployment are on the rise, migrants strive to earn a living through self-employment in the informal sector. This is because migrants encounter difficulties in being incorporated into the formal sector. In South Africa, migrants’ trading dominates the informal sector markets making it of great significance to the country’s socio-economic development. However, the growth and expansion of foreign owned businesses remain a challenge. This study explored the experiences of African migrant traders operating in Pretoria central. African informal migrant traders; street vendors, spaza shop and salon operators were recruited. The study adopted a qualitative approach and a case study research design was used. Purposive sampling technique was used for the recruitment of the participants. 15 participants were recruited from the population of African informal migrant traders who operate their businesses in Pretoria central. In addition, two key informants were recruited; one from the Department of Trade and Industry and one from the Tshwane Barekisi Forum. Data was collected using a semi-structured interview schedule. Thematic analysis was used to analyse the data. The main findings of the study were that African informal migrant traders experienced various challenges including lack of required legal documentation. This posed a threat to achieving significant growth and expansion of their businesses. Therefore, the study concludes that there are some similarities in the challenges experienced by African informal migrant traders and those experienced by the local traders. However, migrant traders experience challenges more severely due to animosity and lack of possession of the required legal documentation.
A report on a research study presented to the Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand, March 2019